Corporate governance, Agency costing, and Dividend policy (An applied study on companies listed on the Damascus Securities Exchange) (Journal of Hama University, 2022)
This research aims to shed light on the impact of the corporate governance on the cash dividends, stock dividends and the agency cost, and determining the impact of the cash dividends, stock dividends on the agency cost in companies listed on the Damascus Securities Exchange during the period (2010-2019). To achieve this objective, the researcher used a Hypothetico-deductive method to formulate the hypotheses; and analyzed the financial statements of all companies listed in Damascus Securities Exchanges. The results of the study showed (1- an inverse effect of corporate governance on stock dividends 2-found a positive effect of corporate governance on cash dividends 3- concluded that corporate governance does not affect the agency cost 4- found that there is an inverse relationship between cash dividends and agency cost in companies listed in the Damascus Stock Exchange.